Pengaruh Peran Keluarga Terhadap Keragaman Pangan Ibu Hamil di Puskesmas Sukowono - Nurul Aini; Sultanah Zahariah (Politeknik Negeri Jember, 2021)
Malnutrition and anemia in pregnant women is one of the nutritional problems in Indonesia. This condition is closely related to the low score of food diversity. Family support, family income and family size take an important role in influencing dietary diversity in pregnant women. This study aims to determine the effect of family income, number of families and family support on food diversity in pregnant women. It is also to analyze the most dominant family factors in influencing dietary diversity among the pregnant women. This research is analytic observational with a cross sectional approach. The population in this study were pregnant women in the second and third trimesters who live in the working area of the Sukowono Public Health Center, Jember regency. The sample size of 82 pregnant women was determined by stratified random sampling. The data in this study were analyzed in two stages, there are bivariate data analysis using simple logistic regression and multivariate analysis using multiple logistic regression. Simple logistic regression analysis showed that the variables of family income, family size and family support had the potential to affect food diversity (p-value < 0.25). The results of multiple logistic regression showed that family size (p-value 0.03) and family support (p-value 0.009) had a significant effect on the dietary diversity of pregnant women. The family income (p-value 0.068) had no significant effect on the food diversity of pregnant women. Family support is the dominant factor that affects the diversity of food in pregnant women because it has the greatest influence with the highest Exp.B value of 2.20. For this reason, it is necessary to increase the efforts to provide information and education to families regarding family support for pregnant women and the importance of food diversity in the hope of preventing and overcoming nutritional problems in Indonesia.